Analysis of Numeracy Literacy Skills of Grade IV Students on Geometry Materials in Elementary Schools - Iruntyasari, Nevy; Nuraini, Ni Luh Sakinah; Mas'ula, Siti (IndoMath: Indonesia Mathematics Education, 2024)
The research was conducted to describe the numeracy literacy abilities of class IV students in geometry material at SDN Kesatrian 1 Malang City and techniques for solving numeracy literacy questions in geometry material. The type of research is qualitative research with a case study method. The data collection technique goes through two stages: tests and interviews. The data collection instruments used in this research were test questions and interview grids. Data analysis using student test result documents and interview results using the Miles & Huberman model, namely data reduction, presentation and conclusion. Students with high numeracy literacy abilities have communication skills and context mathematization abilities, students with moderate numeracy literacy abilities can choose problem-solving strategies but do not carry out communication skills, and students with low numeracy literacy abilities do not meet the indicators for numeracy literacy abilities. The problem-solving technique students use is the formula for the perimeter and area of a rectangle. This research aims to help teachers organize mathematics learning based on numeracy literacy.